An economic assessment of current delivery pathways for the control of tick-borne diseases in Kenya - Ndung'u, L.W.; Randolph, Thomas F.; Coetzee, G.; Krecek, R.C.; Perry, Brian D. (International Society for Veterinary Epidemiology and Economics, 2000)
Smallholder dairy production in Kenya is an important agricultural activity that offers high potential returns contributing to income and employment generation, enhanced food security and improved livelihoods. However, productivity is well below genetic potential and continues to decline. One of the principal constraints to increased dairy output from the smallholder sector is ticks and tick-borne diseases (TBD), with the largest losses due to East Coast fever (ECF). Although several technology packages exist for controlling TBDs, including chemotherapeutic agents, tick control by acaricides, and live vaccines, smallholder farmers continue to experience large losses due to TBDs. Poor uptake of existing control technologies has been attributed primarily to weak or inappropriate delivery systems. Provision of veterinary services to smallholders has traditionally been the responsibility of the state. As public funding has declined over the past two decades, these services have become less effective in meeting farmers needs. The government has responded by encouraging privatization to increase competition and improve efficiency and effectiveness of delivery systems. However, private sector service provision has not developed as anticipated, requiring a continuing role for the public sector. In this study, we apply economic analysis to evaluate current delivery systems and identify opportunities for their improvement.